2015
DOI: 10.3389/fnmol.2015.00065
|View full text |Cite
|
Sign up to set email alerts
|

Post-training activation of Rac1 in the basolateral amygdala is required for the formation of both short-term and long-term auditory fear memory

Abstract: Rac1, a member of the Rho family of small GTPases, is crucial for morphological changes of the mature neuronal synapse including spine formation and activity-dependent spine enlargement, while its role in the formation of associated memories, such as conditioned fear memory, is not clear. Here, we report that selective deletion of Rac1 in excitatory neurons, but not in parvalbumin inhibitory neurons, impaired short- and long-term memories (STM and LTM) of fear conditioning. Conditional knockout of Rac1 before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
1
21
1
Order By: Relevance
“…These results also demonstrate that the level of Rac1 activity in amygdala is critical for the ability to form memory. A study has shown that Rac activity presumably at lower level, as no additional activation during learning or afterwards was applied, can contribute the formation to both STM and LTM 42 whereas we show that high activity of Rac1 inhibits specifically fear LTM. Thus, one conclusion that may be drawn is that individuals with high basal level of Rac1 activity, or at the time of learning, are more resistant for the formation of long-term fear memories.…”
Section: Discussioncontrasting
confidence: 58%
“…These results also demonstrate that the level of Rac1 activity in amygdala is critical for the ability to form memory. A study has shown that Rac activity presumably at lower level, as no additional activation during learning or afterwards was applied, can contribute the formation to both STM and LTM 42 whereas we show that high activity of Rac1 inhibits specifically fear LTM. Thus, one conclusion that may be drawn is that individuals with high basal level of Rac1 activity, or at the time of learning, are more resistant for the formation of long-term fear memories.…”
Section: Discussioncontrasting
confidence: 58%
“…Rac1 is a member of the Rho GTPase family of small G proteins and plays a critical role in regulating actin polymerization in neurons (Etienne-Manneville and Hall, 2002;Heasman and Ridley, 2008;Luo, 2000). Manipulation of Rac1 has been reported to affect synaptic plasticity and behavioral memory in animal models (Gao et al, 2015;Haditsch et al, 2009Haditsch et al, , 2013Hayashi-Takagi et al, 2015;Oh et al, 2010;Tejada-Simon, 2015). We found that both 1-day and 7-day isolation in adult mice induced Rac1 activation in the hippocampus and caused rapid forgetting of social memory without affecting the acquisition of social recognition memory (SRM).…”
Section: Introductionmentioning
confidence: 85%
“…In developing neurons, the activation state of Rac influences lamellipodial extensions of growth cones while in adult neurons, it influences the size and shape of synaptic spines by regulating actin polymerization (Heasman and Ridley, 2008). Through such influences, Rac has been reported to alter synaptic plasticity and behavioral memory in several preparations (Haditsch et al, 2009; Oh et al, 2010; Haditsch et al, 2013; Gao et al, 2015; Tejada-Simon, 2015). …”
Section: The Neuroscience Of Active Forgettingmentioning
confidence: 99%
“…In contrast, Oh et al, (2010) report that genetically enhancing basal Rac1 activity impairs the acquisition of spatial memory and subsequent performance in probe trials. Gao et al, (2015) tested auditory fear conditioning in mice deficient in Rac1 activity in the basolateral amygdala and discovered impaired STM and LTM without altering acquisition. Jiang et al, (2016) have reported that inhibiting Rac in the hippocampus increases memory after massed, contextual fear conditioning, while activating Rac weakens memory produced by spaced, contextual fear conditioning.…”
Section: The Neuroscience Of Active Forgettingmentioning
confidence: 99%